The Ability of Students Develop Narrative Paragraphs by Using Flash Card - Jelita Lumban Gaol (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
This study deals with the student’s ability in writing. Writing is one of the four English language skills which is taught in Indonesia starting from Senior High School. Furthermore, for the students, writing has become a necessary skill to master since it frequently determines their academic success. Therefore, every students has to learn how to write effectively. The scope of the study is limited to the effect of using flash cards in developing student’s ability to write narrative paragraphs. The purpose of this study was to find out whether students, were able to write a narrative paragraph or not. There were 26 students selected with randomly. In choosing the sample from the population, the writer uses lottery technique. The instrument for collecting data was writing test. The data were obtained by administering a self made test as the instruments for collecting the data and were considered in terms of validity and reliability. The method of collecting data plays an important role in conducting any kind of research in order that the result of the study will be valid. To collect the data, the writer used written test to the student as test instrument. Students as observed participants were tested by asking them to write narrative paragraphs based on the flash cards. The results of the writing ability test were analyzed by converting the student’s achievement into percentages. The percentage of the score was obtained based on the five criteria components of writing by using the formula below: The score were evaluated by using Jacob’s (1983) criteria in writing namely: Content, Organization, Vocabulary, Language in Use and Mechanic. After analyzing the data, it was found that 46,16 % or 12 students got the score percentage, lower than 75 %. Therefore, it can be calculated that the students were unable in developing to write narrative paragraph.